Pharmacogenetics of Warfarin in a Diverse Patient Population. (November 2019) - Mak, May; Lam, Carol; Pineda, Sandra J.; Lou, Mimi; Xu, Lilia Yang; Meeks, Christopher; Lin, Cindy; Stone, Roslynn; Rodgers, Kathy; Mitani, Gladys
Introduction: Many warfarin-related genotypes have shown to impact the average daily warfarin (ADW) dose requirements; however, information in non-Caucasian populations is limited. Objectives: To identify the frequencies of 4 warfarin-related gene polymorphisms in an ethnically diverse patient population and to examine their impact with other clinical variables on ADW dose requirements. Methods: Patients were recruited from 2 anticoagulation clinics in the Los Angeles area. Blood samples were collected and genotyped for vitamin K epoxide reductase (VKORC1), CYP2C9*2, CYP2C9*3, and CYP4F2 after informed consent. Charts were reviewed to collect demographic, clinical, and warfarin dosing data. Results: A total of 291 patients were included (120 Caucasians, 127 Hispanics, and 44 Asians). In patients with wild-type genotypes for VKORC1, CYP2C9*2, CYP2C9*3, and CYP4F2, the highest warfarin requirement was found in Caucasians, lower in Hispanics, and lowest in Asians. Homozygous VKORC1 variant carriers were detected in 15%, 15%, and 79% in Caucasians, Hispanics, and Asians, respectively. Progressive lowering of ADW doses were associated with each VKORC1 variant in Caucasians and Hispanics, but the results in wild-type/ heterozygote Asians were unclear. CYP2C9 variants were associated with lower ADW doses; frequencies of CYP2C9*2 and CYP2C9*3 mutations were higher in Caucasians than in Hispanics but rare to none in Asians. The frequencies of CYP4F2 variant were similar across all ethnicities, but their impact on warfarin dose requirement were insignificant. Clinical factors such as age, body surface area, history of coronary artery disease, deep vein thrombosis or atrial fibrillation, and concomitant amiodarone or HMG-CoA reductase inhibitors had varying impact on the ADW requirements in the ethnicities studied. Conclusions: Our study demonstrated differences among 3 ethnic groups in terms of ADW dose requirements and the impact of associated clinical variables. The results suggest that a single model for all ethnicities may not provide the best performance in predicting warfarin dose requirements.